Association of the Vitamin - D Level with Atopic Dermatitis - A Retrospective Case Control Study - Rahul Kumar Sharma, Taruna Singh, (International Journal of Innovative Research in Medical Science, 2017)
Vitamin D has an intense immunomodulatory action on the adaptive immune system and innate immune system; hence it has a great role in the pathogenesis and severity of atopic dermatitis. We studied association of the vitamin D level with atopic dermatitis. The retrospective case control study was conducted at a tertiary care hospital. Retrospective screening of records of atopic dermatitis children and normal (age and sex matched) controls was performed to collect their vitamin-D level during the study period (May 2016 to January 2017). Out of seventy cases of atopic dermatitis of age ≦16 years, 30 patients were found to be investigated for vitamin-D levels. We collected their vitamin-D levels and compared to the vitamin-D levels of thirty controls who attended outpatient department of pediatrics (without any history of skin or chronic systemic diseases). Vitamin-D level and atopic dermatitis are strongly associated (p = 0.002, diagnostic odds ratio- 6.41795% C.I 2.084-19.756, sensitivity 73.33% and sensitivity 70%).